Effects of Parent-Teacher Training on Academic Performance and Parental Anxiety in School-Aged Children With Attention-Deficit/Hyperactivity Disorder: A Cluster Randomized Controlled Trial in Shanghai, China - Shen, Li; Wang, Chunxia; Tian, Yuan; Chen, Jinjin; Wang, Yu; Yu, Guangjun (Frontiers in Psychology, 2021)
Attention-Deficit/Hyperactivity Disorder (ADHD) is the most common chronic neurodevelopmental disorder in childhood, placing a heavy burden on family and society. The treatment of school-aged children with ADHD emphasizes multimodal interventions, but most current research focuses solely on parent training and family functioning. The aim of this study was to examine the effect of parent-teacher training on academic performance and parental anxiety. In an open-label cluster randomized controlled trial from January 2018 to January 2019, 14 primary schools in Shanghai were randomly assigned into the intervention group and the control group, and ADHD screening was conducted for students from grades one to five. Children in both groups received medication as prescribe by their pediatricians. In the intervention group, families and teachers also received parent-teacher training. The training included ADHD behavioral interventions for parents, as well as classroom management skills for teachers. This study screened 9,295 students, 99 children in the control group and 105 children in the intervention group were included in the analysis. The intervention group demonstrated significant improvement in ADHD symptoms and academic performance and decreases in parent stress compared to that in the control group (P < 0.05). This training improved the parents’ perception of ADHD knowledge, treatment options, and drug side effects awareness (P < 0.05). Our study aims to underscore the suitability of such programs in the local nuances of the Chinese context, show application feasibility to pediatricians and psychiatrists, and provide supporting evidence for their utilization within the country’s health and educational systems.